Social pressure in networks induces public good provision - David Jimenez-Gomez (Games, 2021)
I develop a dynamic model with forward looking agents, and show that social pressure is effective in generating provision in a public good game: after a small group of agents start contributing to the public good, other agents decide to contribute as well due to a fear of being punished, and this generates contagion in the network. In contrast to earlier models in the literature, contagion happens fast, as part of the best response of fully rational individuals. The network topology has implications for whether contagion starts and the extent to which it spreads. I find conditions under which an agent decides to be the first to contribute in order to generate contagion in the network, as well as conditions for contribution due to a self-fulfilling fear of social pressure.
Keywords: 330; contagion; public goods; social pressure